The Lvov-Warsaw school-- the new generation - Jadacki, Jacek Juliusz; Paśniczek, Jacek (Poznań studies in the philosophy of the sciences and the humanities, 2006)
"The influence of [Kazimierz] Twardowski on modern philosophy in Poland is all-pervasive. Twardowski instilled in his students a passion for clarity [. . .] and seriousness. He taught them to regard philosophy as a collaborative effort, a matter of disciplined discussion and argument, and he encouraged them to train themselves thoroughly in at least one extra-philosophical discipline and to work together with scientists from other fields, both inside Poland and internationally. This led above all [. . .] to collaborations with mathematicians, so that the Lvov school of philosophy would gradual